Studi Tempat Bertengger Burung Cikalang di Suaka Margasatwa Pulau Rambut - Wardhani, Putri Kesuma; Sukandar, Paskal; Isfaeni, Hanum (Bioma, 2014)
Abstract Frigatebird is one of seabird species found in Pulau Rambut Wildlife Reserve (SMPR). The bird activities include roost in fish pole, flying, foraging in the ocean and also roosting in SMPR at night. The aim of this research was to know roosting site used by frigatebird while at SMPR. This research was conducted in SMPR, Jakarta on August and September 2010 by descriptive method and survey techniques. Data was collected directly on the object of research. Frigatebird population was calculated directly by counting individuals one by one as they flew low in the air over SMPR. Frigatebird roosting site was also researched directly by observing frigatebird when going to roost. Furthermore, vegetation analysis was also conducted on trees in roosting site. Based on our obsevations, the population of frigatebird obtained in SMPR ranged between 87-193 birds. Frigatebird utilize Sterculia foetida tree to be used as a place to roost. This roosting site located in mixed secondary forest to the west and south SMPR close to mangrove forest. Average of height and diameter of S. foetida tree used to roost is 23.47 m and 42.26 cm. There were commonly 3 species of tree of frigatebird roosting site namely Ficus sp. (INP 16.91%), Allophylus cobbe (INP 16.78%) dan Diospyros maritima (INP 14.23). Key words: frigatebird, Pulau Rambut Wildlife Reserve (SMPR), roosting site